Fluid‐Infiltrated Metalens‐Driven Reconfigurable Intelligent Surfaces for Optical Wireless Communications - Ramna Khalid; Jaekyung Kim; Nasir Mahmood; Humberto Cabrera; Muhammad Qasim Mehmood; Aaron Danner; Muhammad Zubair; Junsuk Rho (Advanced Science)
Abstract A reconfigurable intelligent surface (RIS), a leading‐edge technology, represents a new paradigm for adaptive control of electromagnetic waves between a source and a user. While RIS technology has proven effective in manipulating radio frequency waves using passive elements such as diodes and MEMS, its application in the optical domain is challenging. The main difficulty lies in meeting key performance indicators, with the most critical being accurate and self‐adjusting positioning. This work presents an alternative RIS design methodology driven by an all‐silicon structure and fluid infiltration, to achieve real‐time control of focal length toward a designated user, thereby enabling secure data transmission. To validate the concept, both numerical simulations and experimental investigations of the RIS design methodology are conducted to demonstrate the performance of fluid‐infiltrated metalens‐driven RIS for this application. When combined with different fluids, the resulting ultra‐compact RIS exhibits exceptional varifocal abilities, ranging from 0.4 to 0.5 mm, thereby confirming the adaptive tuning capabilities of the design. This may significantly enhance the modulation of optical waves and promote the development of RIS‐based applications in wireless communications and secure data‐transmission integrated photonic devices.